Root-Derived Endophytic Diazotrophic Bacteria Pantoea cypripedii AF1 and Kosakonia arachidis EF1 Promote Nitrogen Assimilation and Growth in Sugarcane - Singh, Rajesh Kumar; Singh, Pratiksha; Guo, Dao-Jun; Sharma, Anjney; Li, Dong-Ping; Li, Xiang; Verma, Krishan K.; Malviya, Mukesh Kumar; Song, Xiu-Peng; Lakshmanan, Prakash; Yang, Li-Tao; Li, Yang-Rui (Frontiers in Microbiology, 2021)
Excessive, long-term application of chemical fertilizers in sugarcane crops disrupts soil microbial flora and causes environmental pollution and yield decline. The role of endophytic bacteria in improving crop production is now well-documented. In this study, we have isolated and identified several endophytic bacterial strains from the root tissues of five sugarcane species. Among them, eleven gram-negative isolates were selected and screened for plant growth-promoting characteristics i.e., production of siderophores, indole-3-acetic acid (IAA), ammonia, hydrogen cyanide (HCN), and hydrolytic enzymes, phosphorus solubilization, antifungal activity against plant pathogens, nitrogen-fixation, 1-aminocyclopropane-1-carboxylic acid deaminase activity, and improving tolerance to different abiotic stresses. These isolates had nifH (11 isolates), acdS (8 isolates), and HCN (11 isolates) genes involved in N-fixation, stress tolerance, and pathogen biocontrol, respectively. Two isolates Pantoea cypripedii AF1and Kosakonia arachidis EF1 were the most potent strains and they colonized and grew in sugarcane plants. Both strains readily colonized the leading Chinese sugarcane variety GT42 and significantly increased the activity of nitrogen assimilation enzymes (glutamine synthetase, NADH glutamate dehydrogenase, and nitrate reductase), chitinase, and endo-glucanase and the content of phytohormones gibberellic acid, indole-3-acetic acid, and abscisic acid. The gene expression analysis of GT42 inoculated with isolates of P. cypripedii AF1 or K. arachidis EF1 showed increased activity of nifH and nitrogen assimilation genes. Also, the inoculated diazotrophs significantly increased plant nitrogen content, which was corroborated by the 15N isotope dilution analysis. Collectively, these findings suggest that P. cypripedii and K. arachidis are beneficial endophytes that could be used as a biofertilizer to improve plant nitrogen nutrition and growth of sugarcane. To the best of our knowledge, this is the first report of sugarcane growth enhancement and nitrogen fixation by gram-negative sugarcane root-associated endophytic bacteria P. cypripedii and K. arachidis. These strains have the potential to be utilized as sugarcane biofertilizers, thus reducing nitrogen fertilizer use and improving disease management.